Relationship between Perceived Physical Competence and Outdoor Play among Children Aged 9-12 Years-Focused Sex-Specific Differences - Ryo Goto; Kazufumi Kitagaki; Kana Horibe; Kazuya Tamura; Naoki Yamada; Rei Ono (MDPI AG, 2023)
Background: Outdoor play (OP), which is considered important for children's development, is declining every year. Perceived physical competence (PPC) is a vital factor that promotes physical activity such as OP, sports clubs, etc., but the relationship between PPC and OP was unknown. The purpose of this research was to investigate the relationship between PPC and OP in children and consider whether there were any sex-specific changes. Methods: A cross-sectional study was conducted in Japan with 288 children (134 girls, age: 10.6 ± 1.01 years). OP was assessed using an original self-report questionnaire. Each weekday, the children reported the time of OP and were classified as "high" if they played outside for at least an hour three times. PPC was evaluated with a self-report questionnaire developed by Okazawa et al. (1996). It has 12 questions and was assessed on a 5-point Likert scale. After adjusting for age, sex, BMI, screen time, sports club participation, and the number of friends, logistic regression analyses were carried out. Results: Children with better PPC were significantly more likely to be classified as "high" [crude odds ratio (OR): 1.04; 95% confidence interval (CI): 1.00-1.08; adjusted OR: 1.04; 95% CI: 1.00-1.08]. Only girls with better PPC were significantly more likely to be classified as "high" in a sex-based stratified analysis [crude OR: 1.08; 95% CI: 1.01-1.15, adjusted OR 1.09; 95% CI: 1.02-1.17]. Conclusions: Particularly among girls, OP could be promoted as a voluntary physical activity with improved PPC.